Perancangan Interior Kapal Pesiar Cinta Laut - Florencia Dewi Marcelina; Yusita Kusumarini (Intra, 2014)
Ship is the oldest transportation tools in the world. Compared to others transportation tools ships need the longest time to get to their destination. Because this reason by the time ship is completed with others function, such as recreation facilities. When the passengers are on the sea they need facilities that can accommodate their needs. Design method that is used in this design proggres are plan, design, develop, and deploy. Concept for this ship’s design is Inforgettable. This concept concern on giving the passengers unforgettable trip. This concept is presented with Papua culture theme. So it can introduce Indonesian traditional culture which isn’t well known. Combine the Papua culture theme and presented in modern way make post-modern stlye. Final result for this interior design is maquette with 1:50 scale.